2020
DOI: 10.1002/2211-5463.12981
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs associated with a mouse model of concanavalin A‐induced autoimmune hepatitis: preliminary screening and comprehensive functional analysis

Abstract: Here, we investigated differentially expressed circular RNAs in a concanavalin A ‐induced AIH mouse model with microarray, identifying differentially expressed circular RNAs that may play crucial roles in the pathogenesis of AIH. These candidates may have potential for development into novel therapeutic biomarkers for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…First, high-throughput detection techniques on screening the differentially expressed genes (involving the coding RNA and non-coding RNA) can be applied to this model, just like the research we are doing, to further explain the interaction between signal transduction pathways [ 61 , 89 , 90 ]. In particular, much more attention should be paid to the differentially expressed genes enriched in signaling pathways associated with T cell activation and NF-κB transcription.…”
Section: Application Prospect and Possible Improvementsmentioning
confidence: 99%
“…First, high-throughput detection techniques on screening the differentially expressed genes (involving the coding RNA and non-coding RNA) can be applied to this model, just like the research we are doing, to further explain the interaction between signal transduction pathways [ 61 , 89 , 90 ]. In particular, much more attention should be paid to the differentially expressed genes enriched in signaling pathways associated with T cell activation and NF-κB transcription.…”
Section: Application Prospect and Possible Improvementsmentioning
confidence: 99%
“…Zheng et al found that hsa_circ_402458, the sponge of hsa-miR-522-3p and hsa-miR-943, was significantly higher in PBC patients not treated with ursodeoxycholic acid (UDCA) than in those treated with it [119]. Liu et al recently reported that the pathogenesis of AIH may involve the mmu_circ_0001520/mmu-miR-193b-3p/MAPK10 axis [120]. However, the role of circRNAs in PSC has not yet been reported.…”
Section: Autoimmune Liver Diseasementioning
confidence: 99%